The performance of Banten Province BPMP employees is reviewed from competency and discipline variables through work culture as an intervening variable - Setiawan, Agus (Institute of Computer Science (IOCS), 2023)
The performance of civil servants, both in central and regional government, is currently receiving major attention due to declining performance. The decline in civil servant performance must be immediately addressed by superiors or stakeholders in each agency. The Men-PAN RB statement confirmed that around 50% and half experienced a decline in performance. This situation must not continue, because it will damage the efficiency of civil servants in several agencies and thereby also reduce work productivity. With the decline in the performance of Banten Province BPMP employees, it can be seen from the gap in employee competency and employee discipline. Where employees must have individual competence to support performance in order to achieve the Banten Province BPMP work programs. And the level of employee discipline must be further increased by looking at employee attendance data, completing work according to predetermined time targets and not being absent during working hours. And the work culture implemented by BPMP Banten Province can encourage employees to be more optimal, effective and efficient in improving performance.